THE ECONOMY OF UKRAINE’S REGIONS IN THE CONDITIONS OF FULL-SCALE WAR: THE LATEST TRENDS (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Over the last decade, Ukraine has been in an extremely difficult geopolitical and socio-economic situation. The problems began in 2014 after the occupation of 7% of the territory by the russian federation, where 13% of Ukrainian population lived and 13.7% of the GDP was formed (in 2013). Russia's armed aggression against Ukraine, which began on the 24th of February, 2022, caused large-scale destruction of production capital and infrastructure, brought significant human victims and social losses. The war led to a reduction in jobs and incomes, a decrease in purchasing power and the amount of accumulated assets. The purpose of the article is to determine the latest development trends in the economy of Ukraine’s regions, caused by the influence of full-scale russian armed aggression. In this context, the transformation of Ukraine’s GDP structure (by types of economic activity) that took place during 2022 was analyzed. Changes in the performance indicators of the construction (in the field of residential and non-residential construction) and transport sectors of the national economy in the regional section are diagnosed. A detailed dynamics assessment of the sold products’ volume in the Ukrainian processing industry, in particular, the metallurgical industry, was carried out. The vectors were established and the amount of changes in the dynamics of Ukraine's foreign economic operations, which caused a decrease in the ratio of commodity exports to imports, was calculated. The export specialization of Ukraine’s regions by main product groups was determined. It was established that the key trends in the formation and development of Ukrainian export potential, except of the geographical reorientation of the export of goods in the European direction (the share of EU countries in the structure of domestic exports increased by 1.6 times during 2022 – up to 63% against 39.4% in 2021), are mainly negative and, at the same time, interdependent, namely: a decrease in the share of high-tech products in the structure of commodity exports with a deepening of the latter's raw material orientation; displacement of domestic producers from traditional market segments as a result of their loss of competitive advantages; little possibility of occupying new market segments with products of low-tech industry segments; dependence on cyclical fluctuations and external factors of not only economic, but also geopolitical origin; excessive energy and resource consuming intensity of domestic production and its dependence on high-tech imports. Prospects for further research in this scientific direction are envisioned in the methodological and analytical substantiation of strategic development priorities in the economy of Ukraine’s regions in the conditions of increasing global challenges and threats.
Keywords: economy, construction, industry, products, production, export, import, regions